Everyday movement - Leung, Gigi, 1976- (Riverhead Books, an imprint of Penguin Random House LLC, 2026)
"On a weekend morning, college roommates Ah Lei and Panda wake up with very different reactions to the night before. They have been chased and tear-gassed in the streets of their city after joining tens of thousands of others to protest a national security law that would effectively spell the end of democracy in Hong Kong. Ah Lei can't get out of bed, her heart heavy with the lingering images of the police and the violence on the streets, and her worries about the future of her hometown. Panda, whose resistance is no less ardent, puts on a sundress, lines her eyes, and urges Ah Lei to join her for brunch. While the demonstrations rage, the routine of life also persists for Ah Lei, Panda, and people in their orbits. They attend family gatherings, fight with their mothers, try and fail to focus at work on Mondays, and make time for dinner dates and app hookups. But the looming political tension and anxiety for the future transform such everyday encounters. In the span of a few months, life as they know it seems to become a mirage: the comfort of air-conditioned shopping malls is disrupted by bloodshed; tear gas and the sounds of rubber bullets amid neon signs strangely evoke happier memories of summer night fireworks."--